Proceso de elaboración del biofertilizante “Pasto fermentado” con microorganismos de montaña - Montero Acurio, Ronny Daniel (2019)
SUMMARY The present work consisted in the elaboration of a biofertilizer of natural and / or organic origin, using as an inoculum source the tender grass leaves, as an alternative for the preservation and reproduction of the soil microbiotics, In the fermented grass, the MM are those in charge of favoring the fermentation of the materials and reproducing a greater quantity of beneficial microorganisms that are subsequently occupied, in the elaboration of the organic fertilizers are these solids or liquids. The technique for the preparation of the biofertilizer was developed in the premises of the "Faculty of Agricultural Sciences" of the Technical University of Babahoyo Province of Los Ríos, located at kilometer 7½ of the Babahoyo - Montalvo highway. Whose objectives prevailed in the capture of effective microorganisms, to then reproduce them through the fermented grass technique. And considering what has been developed and researched in the present work, it is concluded that fermented grass is a source of inoculum of mountain microorganisms (MM), which consists of producing a substitute for fresh cow dung. Considering that farmers focus as a main factor in the crops that sow the fertility and productivity of agricultural soils, it is recommended: Promote training campaign for the preparation of bioferments based on green material (grass) plus MMA.